High-fat diet promotes gestational diabetes mellitus through modulating gut microbiota and bile acid metabolism - Yao, Lei; Zhou, Xuefei; Jiang, Xianqi; Chen, Hao; Li, Yuanliang; Xiong, Xiao; Tang, Yan; Zhang, Haogang; Qiao, Pengfei (Frontiers in Microbiology, 2025)
IntroductionGestational diabetes mellitus (GDM) is a condition characterized by glucose intolerance during pregnancy, estimated to affect approximately 20% of the whole pregnancies and is increasing in prevalence globally. However, there is still a big gap in knowledge about the association between gut microbiota associated metabolism alterations and GDM development.MethodsAll the participants accomplished the validated internet-based dietary questionnaire for Chinese and serum, fecal samples were collected. HFD, control diet or colesevelam intervention was fed to GDM mice models or Fxr-/- mice models, with or without antibiotics cocktail treatment. Fecal microbiota transplantation were used for further validation. Gut microbiota and metabolites were detected by metagenomic sequencing and high-performance liquid chromatography-mass spectrometry, respectively. Bile acids of serum, fecal samples from human and mice were analysised. Body weight, average feed intake, blood glucose, insulin levels and oral glucose tolerance test was performed among each groups. Expression levels of Fxr, Shp and Fgf15 mRNA and protein were detected by quantitative reverse transcription polymerase chain reaction and western blot, respectively.ResultsOur data indicated that high fat diet (HFD) was linked with higher prevalence of GDM, and HFD was positively associated with poor prognosis in GDM patients. Moreover, compared with normal diet (ND) group, GDM patients from HFD group performed a loss of gut microbiota diversity and enrichment of Alistipes onderdonkii, Lachnospiraceae bacterium 1_7_58FAA, and Clostridium aspaaragiforme while ruduction of Akkermansiaceae, Paraprevotell xylaniphila, and Prevotella copri. Additionally, HFD aggravated GDM in mice and gut microbiota depletion by antibiotics crippled the effect of excess fat intake. BAs profile altered in HFD GDM patients and mice models. Fecal microbiota transplantation (FMT) further confirmed that gut microbiota contributed to bile acids (BAs) metabolic dysfunction during HFD-associated GDM development. Mechanically, HFD-FMT administration activated Fxr, Shp, and Fgf15 activity, disturbed the glucose metabolism and aggravated insulin resistance but not in HFD-FMT Fxr−/− mice and ND-FMT Fxr−/− mice. Furthermore, colesevelam intervention alleviated HFD-associated GDM development, improved BAs metabolism, suppressed Fxr, Shp, and Fgf15 activity only in WT mice but not in the Fxr−/− HFD + Colesevelam group and Fxr−/− HFD group. HFD induced GDM and contributed to poor prognosis in GDM parturients through inducing gut microbial dysbiosis and metabolic alteration, especially appeared in BAs profile. Moreover, Fxr pathway participated in regulating HFD-associated gut microbiota disordered BAs metabolites and aggravating GDM in mice.DiscussionModulating gut microbiota and BAs metabolites could be a potential therapeutic strategy in the prevention and treatment of HFD-associated GDM.